2015
DOI: 10.4103/0974-8490.159577
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical screening of phyllanthus amarus ethanolic extract for its analgesic and antimicrobial activity

Abstract: Background:To discover a new agent which possesses dual property of analgesic and antimicrobial activity, thereby reducing the burden of polypharmacy. Phyllanthus amarus was screened for its analgesic and antimicrobial activities.Objectives:The objective was to evaluate the analgesic and antimicrobial activity, of P. amarus ethanolic extract (PAEE).Materials and Methods:The ethanolic extract of P. amarus was prepared using Soxhlet apparatus. An in vivo study using Swiss albino mice was done to screen the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…It was also reported that intrathecal administration of dopamine has shown antinociceptive effects in rat tail flick test. [ 1 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also reported that intrathecal administration of dopamine has shown antinociceptive effects in rat tail flick test. [ 1 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…On 14 th day, after the pharmacological experiments, animals were euthanized and brain dopamine levels were estimated using the method described by Bhat et al . [ 1 ] The method is described briefly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazilian forests, especially the Amazon rainforest, represent the largest source of plant species in the world, many of which have medicinal benefits. Along with such biodiversity, the Brazilian population also has a very rich folk medicine, preserved by traditional communities, which provides valuable information, useful to the selection of species for pharmacological screening (Hegde et al, 2014;Moraes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Plants inserted in traditional medicine have interested scientific community as a source of new bioactive substances discovery for human disorders treatment (Novais et al, 2003; Samy et al, 2008). In this sense, plants with therapeutic potential are a promising strategy for the development of anti-inflammatory drugs in search of a better therapy, reinforcing the importance of ethnopharmacological knowledge (Gupta et al, 2006; Phanse et al, 2012; Hegde et al, 2014).…”
Section: Introductionmentioning
confidence: 99%